Emerging functional cross-talk between the Keap1-Nrf2 system and mitochondria - Itoh, Ken (J Clin Biochem Nutr, 2015)
Nuclear factor erythroid-derived 2-related factor 2 (Nrf2) was originally identified as a positive regulator of drug detoxifying enzyme gene expression during exposure to environmental electrophiles. Currently, Nrf2 is known to regulate the expression of hundreds of cytoprotective genes to counteract endogenously or exogenously generated oxidative stress. Furthermore, when activated in human tumors by somatic mutations, Nrf2 confers growth advantages and chemoresistance by regulating genes involved in various processes such as the pentose phosphate pathway and nucleotide synthesis in addition to antioxidant proteins. Interestingly, increasing evidence shows that Nrf2 is associated with mitochondrial biogenesis during environmental stresses in certain tissues such as the heart. Furthermore, SKN-1, a functional homolog of Nrf2 in C. elegans, is activated by mitochondrial reactive oxygen species and extends life span by promoting mitochondrial homeostasis (i.e., mitohormesis). Similarly, Nrf2 activation was recently observed in the heart of surfeit locus protein 1 (Surf1) -/- mice in which cellular respiration was decreased due to cytochrome c oxidase defects. In this review, we critically examine the relationship between Nrf2 and mitochondria and argue that the Nrf2 stress pathway intimately communicates with mitochondria to maintain cellular homeostasis during oxidative stress.